DEVELOPMENT OF TITANIUM DIOXIDE BASED SOLAR CELL BY ADDITION OF IMPURITY AND COPPER PARTICLE INSERTION USING PULSE VOLTAGE ELECTROPLATING METHOD - ROKHMAT (NIM : 30212005), MAMAT
Efficiency improvement of TiO2 based solar cells has been done successfully by adding copper (II) nitrate trihydrate (Cu-NT) and copper oxide (CuO) particle impurity to TiO2 layer. This solar cell is a multilayer sandwich containing a transparent conducting electrode (TCO), a TiO2 active layer, a polymer electrolyte as a hole transport medium and an aluminum as a counter electrode. The solar cell efficiencies increased up to 0.04% and 0,17% for the addition of Cu-NT and CuO particles to TiO2 layer, respectively. Efficiency of the cell increases with the weight fraction of Cu-NT and CuO particles that was added to TiO2 layer until achieve the optimum value, i.e. when the weight fraction of Cu-NT at 1.4% wt and CuO particles at 1.8% wt. The presence of an impurity is able to improve the absorption spectrum of the TiO2 layer so as to improve the performance of the solar cells. To improve the electron transport process that has been generated in the TiO2 layer, the insertion of copper (Cu) particles on the space between the particles of TiO2 was used. The insertion of copper particles was performed on the TiO2 layer containing of 1.4 %wt of Cu-NT using a traditional electroplating method (TEP) with a constant voltage source of 5 volt for 10 seconds. The efficiency of 0.35% and the fill factor (FF) of 0.31 was achieved after the insertion of the copper particles, where the number of copper particles content was 5.77%. The presence of copper particles is able to improve electron transport process to quickly move to the primary electrode, thereby reducing the recombination between electron and hole. Pulse voltage electroplating method (PVEP) was developed to control the particle content of copper that was inserted in the TiO2 layer. Copper particle content can be controlled by setting the duty cycle and the time of electroplating. Solar cell performance improvement was achieved by insertion of a copper particle using this PVEP method. By using a duty cycle of 60% for 30 seconds, the highest efficiency solar cells can be achieved up to 2.21% with a FF of 0.30. Development of a mathematical model was proposed to explain the dependence of copper particles content to the solar cells efficiency. The proposed model also has a closeness with experimental data obtained. Treatment of solar cells with NaOH was performed to improve the performance of solar cell. The efficiency of the cell improves to 3.5% and and the FF of 0.40 after NaOH post-treatment. This improvement occurred due to the addition of Na+ ions which increases the ionic conductivity of the electrolyte. Besides, when the posttreatment is performed, a high specific surface area is generated in the aluminum counter electrode. Consequently, this will improve the contact between aluminum and the electrolyte.